Artesãs do povoado de Jacunã – Jaguarari – BA: uma proposta de organização da produção - Silva, Gracione Rocha da (2016)
This research report presents the result of the work with the members of the Association of Artisans of the village of Jacunã, located in the municipality of Jaguarari, state of Bahia. It is an intervention research that had the objective to register the artisanal production and its singularity, as well as exposing the production process, understanding the place that this activity occupies in the life of the artisans and the meaning it has in their daily lives, from the form of organization and commercialization of the craftsmanship developed by this association, since the year 2008.The straw work, developed by the women of the association, is an alternative to the need to generate income. This research used a qualitative and interventionist approach, through the accomplishment of the participatory diagnosis, with the use of workshops and semi-structured interviews. The target audience of this work was composed by the members of the Artisan Association of Jacunã. This intervention research resulted in the reflection on the organization of the artisans of the Town of Jacunã through their association, stimulated the qualification and diversification of production and the choice of the fancy name, besides the search for the expansion of the commercialization spaces of its products. In theoretical terms, he conjectured on the importance of female participation in contemporary society and in the spaces of production, from the perspective of gender studies. This study also observed that straw handicrafts have a cultural relationship with female activity in the village, and forming, finally, a real and positive possibility of promoting the autonomy of rural women, as well as an instrument for generating income and valuing women's work.